Copolymerization of ring-opening oxaspiro comonomer with denture base acrylic resin by free-radical/cationic hybrid polymerization - Ranganathan Ajay; Vikraman Rakshagan; Murugesan Sreevarun; Dharanividhya Bhuvaneshkumar; Sekaran SajidaBegum; Veerakumar Vignesh (Wolters Kluwer Medknow Publications, 2021)
Background: Polymerization shrinkage is an innate characteristic of thermo-polymerized denture base acrylic resin. Volumetric shrinkage is still a problem, although myriad material modifications. Ring-opening oxaspiro monomers have promising volumetric expansions of about 7%. These monomers have diminished the shrinkage in dental filling resins through copolymerization (CP). However, their CP with denture base resins is not reported yet. Purpose: The aim is to confirm the CP of an oxaspiro monomer with methyl methacrylate (MMA) by radical-cationic hybrid polymerization and to assess the degree of conversion (DC) of the formed copolymer. Materials and Methods: The oxaspiro monomer was synthesized by a transesterification reaction. The study groups were based on the composition and thermo-polymerization method. The control and E1 groups were thermo-polymerized in water-bath, whereas the E2 group in a laboratory autoclave. Both E1 and E2 groups contained the oxaspiro monomer and cationic initiator. E2 group had an additional radical initiator. The CP and DC were confirmed and assessed by infrared spectroscopy. Results: Accentuation of carbonyl peak, the disappearance of the spiro-carbon peak, and the appearance of ether linkages in experimental groups confirmed the ring-opening. E2 group had the highest DC. Conclusion: The oxaspiro monomer successfully copolymerized with MMA and had good DC.